Gambaran Perilaku Kesehatan Reproduksi pada Siswa SMA di Kota Kupang Tahun 2019 - Beatrice Palang Demon; Indriati A. T. Hinga; Amelya B. Sir (Lontar : Journal of Community Health, 2019)
Good reproductive health will improve reproductive health and prevent reproductive health problems. The Indonesian Family Planning Association survey and On Track Media Indonesia (OTMI) found that around 29% to 31% of adolescents in East Nusa Tenggara had premarital sex. The impact of poor reproductive health behavior is unwanted pregnancy and sexually transmitted infection. This is a quantitative descriptive study that aimed to describe reproductive health behavior in high school students in Kupang City. The population in this study were high school students from grade XI and XII (6863 students) and a sample of 378 students taken by proportionate stratified random sampling technique. The results showed a description of Genital Personal Hygiene behavior in high school students in Kupang City as good is 249 students (66%), while less is 129 students (34%). The pre-marital sexual behavior of high school students in Kupang City was at a risk is 85 students (29%) and 293 students (71%) were not at risk. The behavior of watching porn videos for high school students in Kupang City is 217 students (57.4%) have watched and 161 students (42.6%) have not watched porn videos/movies. Behavior discussing reproductive health among high school students in Kupang City is 216 students (57%) discussing reproductive health and 162 students (43%) do not discuss reproductive health. The Schools can give information about reproductive health to students by optimizing the program of Information and Counselling Center (PIK) that already available.